2022
DOI: 10.1186/s12864-022-08795-z
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA sequencing of Embryonic Myogenesis in Chengkou Mountain Chicken

Abstract: Background Skeletal muscle tissue is among the largest organ systems in mammals, essential for survival and movement. Embryonic muscle development determines the quantity and quality of muscles after the birth of an individual. MicroRNAs (miRNAs) are a significant class of non-coding RNAs that bind to the 3’UTR region of mRNA to regulate gene function. Total RNA was extracted from the leg muscles of chicken embryos in different developmental stages of Chengkou Mountain Chicken and used to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Integrated analysis of lncRNA and mRNA expression profiles revealed that lncRNAs and target genes that might contribute to the regulation of different embryonic stages of skeletal muscle development in chicken ( Li et al, 2016 ; Wu et al, 2022 ). Many miRNAs related to embryonic muscle development identified in Chengkou mountain chicken were also found in Tibetan chicken ( Shi et al, 2022 ). We have not found research on circRNA sequencing related to embryonic muscle development in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated analysis of lncRNA and mRNA expression profiles revealed that lncRNAs and target genes that might contribute to the regulation of different embryonic stages of skeletal muscle development in chicken ( Li et al, 2016 ; Wu et al, 2022 ). Many miRNAs related to embryonic muscle development identified in Chengkou mountain chicken were also found in Tibetan chicken ( Shi et al, 2022 ). We have not found research on circRNA sequencing related to embryonic muscle development in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…As a correlate, the production of cytokines, ROS, and infiltration of immune cells lead to the destruction of target tissues [ 292 ]. To mitigate these conditions, immunomodulation approaches are at the center of attention [ 293 ]. Recent studies have therefore focused much attention on the area of local immunomodulation through various immunomodulatory nanosystems (IMNs) [ 291 ].…”
Section: Local Immunomodulation In Muscular Tissue Using Hydrogelsmentioning
confidence: 99%
“…Recent studies have therefore focused much attention on the area of local immunomodulation through various immunomodulatory nanosystems (IMNs) [ 291 ]. In general, IMNs have been developed from engineered NPs, small drugs, nanomaterials, and biomaterials, factors such as cytokines, antibodies, siRNA, extracellular vesicles, and polysaccharides [ 100 , 292 , 293 ]. It was suggested that scaffolds provide a platform for immune cell adhesion, proliferation, and differentiation.…”
Section: Local Immunomodulation In Muscular Tissue Using Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations